Who are the relevant stakeholders to the local government context? empirical evidences on environmental influences in the decision-making process of english local authorities - Ricardo Gomes Corrêa (BAR - Brazilian Administration Review, 2004)
This article presents empirical evidence of stakeholding in the local government context. It is the result of asurvey carried out with English Local Authorities in 2001. It outlines the arena in which local government makedecisions by pinpointing the relevant stakeholders in the process as well as the amount of power they areperceived to represent by chief executives. The investigation has its theoretical basis in resource dependence andinstitutional theories, which are commonly used for explaining an organizations behaviour and performance asinfluenced by its environment. As an empirical contribution, the article proposes a stakeholder map for any kindof local government organizations that will help in identifying strategies for managing stakeholders.